The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10705-009-9266-7
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization following surface application of raw and treated liquid swine manure

Abstract: The treatment of liquid swine manure (LSM) is primarily intended to produce energy and/ or decrease P concentration in the liquid fraction, but may have a simultaneous impact on its potential for N volatilization. We compared NH 3 volatilization in the field following surface application (May 2004; May 2005; September 2005) of untreated LSM and the liquid fraction of LSM (hereafter called treated LSM) that had undergone either natural decantation, filtration, anaerobic digestion, or anaerobic digestion ? flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…These values are in good agreement with those reported by Misselbrook et al (2005b) for field application of pig slurry with low TS content. Our study also confirms the tendency of the separated liquid fraction to emit lower proportions of applied TAN as NH 3 -N than raw slurry following land application, previously observed by other authors (e.g., Søgaard et al, 2002;Sommer et al, 2003;Misselbrook et al, 2005b;Balsari et al, 2008b;Balsari et al, 2009;Chantigny et al, 2009;Monaco et al, 2011). This was attributed to the low TS content in the liquid fraction, which permitted a more rapid infiltration of the TAN into the soil (Sommer and Hutchings, 2001).…”
Section: Application Trialssupporting
confidence: 91%
“…These values are in good agreement with those reported by Misselbrook et al (2005b) for field application of pig slurry with low TS content. Our study also confirms the tendency of the separated liquid fraction to emit lower proportions of applied TAN as NH 3 -N than raw slurry following land application, previously observed by other authors (e.g., Søgaard et al, 2002;Sommer et al, 2003;Misselbrook et al, 2005b;Balsari et al, 2008b;Balsari et al, 2009;Chantigny et al, 2009;Monaco et al, 2011). This was attributed to the low TS content in the liquid fraction, which permitted a more rapid infiltration of the TAN into the soil (Sommer and Hutchings, 2001).…”
Section: Application Trialssupporting
confidence: 91%
“…However, there are contradictory reports from the literature (Möller, 2015) suggesting that emissions are related to the feedstocks and soil properties to which they are applied, e.g., soil organic matter content, soil texture, water content, and aeration (Chantigny et al, 2009;Eickenscheidt et al, 2014). Reported N losses as N 2 O emissions following the application of food-based digestate vary from 0.45% (Nicholson et al, 2017) to 4-10% (Tiwary et al, 2015) of the total N applied.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that swine manure hosts and reservoirs human pathogenic bacteria, including Clostridium perfringens, Escherichia coli, and Salmonella spp., among others [3]. Other problems associated with swine manure are odours caused by gases produced by decomposing manure in swine manure handling facilities or from land application [4]. Nutrients leaching below the root zone and into groundwater together with nutrients entering into surface water systems through runoff from manure storage facilities are other concerns caused by improper swine manure management.…”
Section: Introductionmentioning
confidence: 99%